Electric Car Charging Problem - Qurbonazarov Sukhrob Erkin ugli (Periodica Journal, 2022)
Electric car charging methods are one of the latest technologies used today. While not a groundbreaking contribution to the genre, it is certainly a work in progress. Wireless support is more convenient than wired support devices. With such devices, the driver who arrives at the charging station does not have to get out of the car. This is because when the wireless charging point is reached and the car is parked in the right place, it will automatically start charging and has similar advantages. The following is a summary of most of the wired charging stations
Keywords: current; AC; Factory mode